2021
DOI: 10.1111/gcb.15540
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for increased loss of old carbon in a temperate organic soil after 13 years of simulated climatic warming despite increased CO2 emissions

Abstract: Determining the temperature sensitivity of terrestrial carbon (C) stores is an urgent priority for predicting future climate feedbacks. A key aspect to solve this long‐standing research gap is to determine whether warmer temperatures will increase autotrophic activities leading to greater C storage or promote heterotrophic activities that will drive these systems to become C sources. We experimentally addressed this critical question by subjecting intact plant‐soil systems in a UK upland ecosystem to simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In contrast to real Q 10 described by Arrhenius law, the apparent Q 10 , which reflects substrate availability and is described by Michaelis–Menten equation, decreased linearly with declining C availability (Gershenson et al, 2009; Li et al, 2020). Other studies demonstrated that Q 10 is independent on soil depth (Briones et al, 2021; Fang et al, 2005; Hicks Pries et al, 2017). These findings, however, could result from the narrow range of [ S ] in the soils they tested.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to real Q 10 described by Arrhenius law, the apparent Q 10 , which reflects substrate availability and is described by Michaelis–Menten equation, decreased linearly with declining C availability (Gershenson et al, 2009; Li et al, 2020). Other studies demonstrated that Q 10 is independent on soil depth (Briones et al, 2021; Fang et al, 2005; Hicks Pries et al, 2017). These findings, however, could result from the narrow range of [ S ] in the soils they tested.…”
Section: Discussionmentioning
confidence: 92%
“…Preferential substrate use could therefore also shape C cycling at the ecosystem scale. For example, in a large-scale warming experiment in the UK, Briones et al (2021) found no evidence for positive priming, while enhanced turnover of recently fixed C suggests that preferential substrate use can take place at the landscape scale. While substrate use was mostly independent from substrate C:N, it was idiosyncratic of land cover type and soil horizon (Fig.…”
Section: Preferential Substrate Use Decreases Priming Effectsmentioning
confidence: 94%
“…In recent decades, it has been widely observed that temperature plays a major role on the dynamics of SOM (Knorr et al, 2005;Davidson and Janssens, 2006;Feng and Simpson, 2008) and the mean age of respired CO 2 (Hopkins et al, 2012;Chen et al, 2021) by increasing the decomposition rates from fast-cycling pools (Trumbore et al, 1996) and mobilizing old C in warming conditions (Dutta et al, 2006;Briones et al, 2010). In contrast, other studies have suggested that warming does not lead to release of old C (Briones et al, 2021;Dioumaeva et al, 2002) and that non-labile C decomposition is insensitive to temperature increase (Liski et al, 1999). By comparison, drying phenomena increased the release of modern 14 CO 2 from shallow soil layers but preserved the old soil carbon pools in deeper layers (Kwon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%